SHARED SOCIAL IDENTITIES, COLLABORATION, AND SOCIAL IDENTITY THEORY: A LITERATURE REVIEW - Ren, Peng; Chong, Wei Ying (INTI International University, 2023)
This paper embarks on a comprehensive exploration of the intricate interplay that exists between shared social identities, collaboration, and the foundational framework of Social Identity Theory (SIT). Through an exhaustive and meticulous analysis of a diverse array of scholarly literature, it endeavors to illuminate the multifaceted and dynamic nature of the relationship between shared identities and collaborative endeavors. Moreover, it underscores the invaluable role of Social Identity Theory (SIT) in elucidating the cognitive processes and motivations that underlie these intricate social interactions. As we navigate the labyrinth of theoretical perspectives, empirical findings, and their real-world implications, this paper offers profound insights into the important function that shared social identities assume in shaping collaborative dynamics across a wide spectrum of contexts. It serves to cast light upon the myriad ways in which our shared identities, whether they derive from cultural, professional, or other affiliations, exert a discernible influence on our modes of engagement with one another and our collective efforts towards shared objectives. In dissecting this intricate interplay, we attain a more profound understanding of the profound impact that our social identities wield over our collaborative initiatives and the broader societal fabric in which they are embedded. This exploration thus contributes significantly to the ongoing discourse on the intricate and interconnected dimensions of social identity, collaboration, and the cognitive underpinnings that drive them.